Synthesis of waste cooking oil based biodiesel via ferric-manganese promoted molybdenum oxide zirconia nanoparticle solid acid catalyst: influence of ferric and manganese dopant - Alhassan, Fatah H.; Rashid, Umer; Yap, Taufiq Yun Hin (Japan Oil Chemists' Society, 2015)
The utilization of ferric-manganese promoted molybdenum oxide/zirconia (Fe-Mn- MoO/ZrO2) (FMMZ) solid acid catalyst for production of biodiesel was demonstrated. FMMZ is produced through impregnation reaction followed by calcination at 600°C for 3 h. The characterization of FMMZ had been done using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), thermal gravimetric analysis (TGA), temperature programmed desorption of NH, (TPD-NH,), transmission electron microscopy (TEM) and Brunner-Emmett-Teller (BET) surface area measurement. The effect of waste cooking oil methyl esters(WCOME's) yield on the reactions variables such as reaction temperature, catalyst loading, molar ratio of methanol/oil and reusability were also assessed. The catalyst was used to convert the waste cooking oil into corresponding methyl esters (95.6%‡0.15) within 5 h at 200°C reaction temperature, 600 rpm stirring speed,1:25 molar ratio of oil to alcohol and 4% w/w catalyst loading. The reported catalyst was successfully recycled in six connective experiments without loss in activity. Moreover, the fuel properties of WCOME's were also reported using ASTM D 6751 methods.